Phytochemical modulation of P-Glycoprotein and its gene expression in an ivermectin-resistant Haemonchus contortus isolate in vitro - Pacheco, Poliana Araújo; Louvandini, Helder; Giglioti, Rodrigo; Wedy, Bruna Costa Rodrigues; Ribeiro, Jessica Carolina; Verissimo, Cecilia José; Ferreira, Jorge Freire da Silva; Amarante, Alessandro Francisco Talamini do [UNESP]; Katiki, Luciana Morita (Elsevier, 2022)
Haemonchus contortus is the most important gastrointestinal nematode in small ruminant systems worldwide and has developed resistance to several drugs, including ivermectin (IVM). IVM is not only a veterinary drug but also a safe, broad-spectrum, antiparasitic drug used in humans. One of the main IVM-resistance mechanisms in H. contortus involves P-glycoprotein (PgP), a trans-membrane transport protein that rids worm cells from toxic molecules. This study aimed to evaluate the anthelmintic activity of IVM, alone or combined with main terpenes of essential oils (alpha-terpinene, beta-citronellol, beta-pinene, citronellal, limonene, menthol, and terpinolene) and with phenolic compounds (epicatechin, epigallocatechin, gallocatechin, pentagalloylglucose, procyanidin, and quercetin). All compounds were tested, alone or combined with IVM, against susceptible (HcS) and resistant (HcR) isolates of H. contortus through the larval development test (LDT) and the adult motility assay (AMT) using verapamil (VP), a known PgP modulator, as a control. Results for the LDT determined that the lethal concentration required to kill 50% of nematodes (LC50) with IVM was 10 times greater (0.01 µg/mL) for HcR than for HcS (0.001 µg/mL). The combination IVM + VP inhibited the activity of PgP in HcR resulting in a LC50 = 0.002 ug.mL−1. Although limonene was the least effective and alpha-terpinene the most effective terpene when tested alone against HcR, the best combinations were IVM + limonene and IVM + quercetin both produced LC50 = 0.002 µg/mL (similar to IVM+VP) which were chosen for subsequent tests. Because adult parasites are the final target for anthelmintics, IVM was evaluated in HcS (LC50 = 0.067 µg/mL) and HcR (LC50 =164.94 µg/mL) through the AMT. Results obtained with IVM + VP (LC50 = 0.020 µg/mL) in HcR were similar to IVM + limonene (LC50 = 0.028 µg/mL) and outperformed IVM + quercetin (LC50 = 1.39 µg/mL). RNA extracts from HcR adult worms exposed to IVM, IVM+VP, and IVM + limonene were evaluated for PgP expression by RT-PCR. For most concentrations, PgP-9 was significantly more expressed in worms treated with IVM alone than in worms treated with IVM + VP or IVM + limonene. Our results suggest that limonene is involved in the modulation of the PgP-9 gene and that it can restore the activity of IVM in the HcR isolate down to levels seen in HcS. Limonene is one of the main compounds found in citrus peel and has the potential to be both safe and affordable if used in combination with IVM to restore its anthelmintic effects against multi-drug-resistant H. contortus isolates. Our results also suggest that we may be more successful by combining natural products with failing commercial anthelmintics than trying to find natural substitutes for them.
Keywords: Anthelmintic resistance; Barber-pole worm; Ivermectin; MDR Haemonchus; PGP modulation; Phenolic compounds; Terpenes